Assessment of Budget Sustainability in Sarawak - Lau, Evan; Puah, Chin-Hong; Teo, Hui-Fern (Asian Economic and Social Society, 2012)
This study reexamines the sustainability of budget stance of Sarawak state, 1970-2008. Using the intertemporal borrowing constraint as a framework, the study tests the long-run relationship between government revenue and expenditure. Empirical results demonstrate a long-run equilibrium relationship among the variables. The cointegration test result suggests that Sarawak state’s fiscal stance satisfies the weak sustainability condition. In addition, the Granger causality test result reveals a bi-directional relationship between government revenue and expenditure. This means that fiscal authorities made simultaneous decisions on expenditure and revenue. Government revenue and expenditure will mutually reinforce each other.